Perilaku Bullying dan Peran Sekolah dalam Mengatasinya (Studi Kasus di SDN 1 Ulu Lapao-Pao) - Kartini Kartini; Abdul Haris Nasution; Muh. Iqbal (Journal on Education, 2024)
Cases of bullying, both verbal and physical, have become a serious issue in the school environment. Violent phenomena such as mocking, taunting, and physical actions need to be addressed with comprehensive preventive measures. This study uses a qualitative research method by adopting a case study approach with the aim of exploring in depth the role of Islamic Religious Education (PAI) teachers in overcoming bullying behavior in primary education institutions (SD), especially at SDN 1 Ulu Lapao-Pao, Kolaka Regency. The Research Results Bullying at SDN 1 Ulu Lapao-pao is divided into several types, namely: Physical: engaging in hurtful physical actions, such as punches, kicks, and pushing in front of the door during play. Verbal: involves distressing treatment, such as demeaning words, even by referring to the names of learners' parents. Psychological: involves threats and exclusion in the classroom, creating fear and loss of friends for the victim of bullying. Cyberbullying: occurs through technological intermediaries, such as messages through applications, such as WhatsApp. The Efforts of Islamic Religious Education Teachers in Overcoming Bullying are 1) detecting and overcoming bullying through strategies such as discussing the concept of justice in Islam, forming good morals, 2) open dialogue with students. 3) holding extracurricular activities based on Islamic values, 4) teachers create an inclusive and safe environment. 5) special attention to bullying perpetrators, involving parents, 6) and psychological strengthening are part of the efforts of Islamic Religious Education teachers to create a harmonious school environment and avoid bullying practices.